Alterations in metabolism and diurnal rhythms following bilateral surgical removal of the superior cervical ganglia in rats - Mul Fedele, Malena L. (2018)
Fil: Mul Fedele, Malena L. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina